ANALYSIS OF FACTORS AFFECTING INVESTMENT IN INDONESIA - Faradlan, Ridwan; Juliannisa, Indri Arrafi; Sugianto, Sugianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the factors that influence investment in Indonesia which is influenced by its effects caused by inflation, interest rates, exchange rates and labor, where the data used is time series data with the OLS method and shows the results that the results of multiple regression analysis show that ( 1) a significant effect of inflation on investment in Indonesia (2) interest rates have a significant effect on investment in Indonesia (3) the exchange rate has a significant effect on investment in Indonesia (4) labor has a significant effect on investment in Indonesia. Keywords: Investment, Inflation, Interest Rate, Exchange Rate and Labor.